Self-generated microporous hydrogel coating on mesoporous silica: A hierarchical porous structure for high-performance HILIC - Shuning Li; Tong Zhang; Xiaojing Liang; Lei Wang; Yong Guo (Analytica Chimica Acta, 2026)

Contribution of dihydroorotate dehydrogenase complex to NADH supply and metabolic flux redirection in Clostridium acetobutylicum - Dandan Jiang; Jihong Yi; Haifeng Zhu; Liangliang Gao; Shuning Wang; Guodong Liu; Lanpeng Li; Quan Zhang; Meng Wang; Armin Ehrenheich; Fuli Li; Yihua Xiao; et al. (Bioresource Technology, 2026)

Voronoi curvature scaffolds rejuvenate senescent stem cells and enhance aged bone regeneration - ZuFu Lu; Renugaa Suresh Babu; Iman Rhohani; Rana Judeh; Shuning Wang; Yiran Zhang; Yufan Zhu; Vimalraj Selvaraj; Swathi Sudhakar; Hala Zreiqat (Chemical Engineering Journal, 2026)

Fluctuations in groundwater inflow induced by periodic fracturing of overlying strata with mining - Shuning Dong; Zhenfang Zhou; Yang Dong; Qiang Ji; Jiankun Xue; Tiantian Wang; Yutong Wang; Le Han; Peiqiang Gao; Shenghu Luo; Yingying Yao (Bulletin of Engineering Geology and the Environment, 2026)

Functional identity of typhoon-derived green litter overrides functional dissimilarity in reshaping litter faunal feeding guilds in a subtropical forest - Shuning Ma; Lifeng Wang; Qingjun Ma; Ajuan Zhang; Rui Cao; Zhuang Wang; Qin Wang; Mei Qin; Wanqin Yang (Plant and Soil, 2026)

Tailoring the surface acidity and electronic structure of (Ce, La)PO4 via Fe modification for low-temperature NH3-SCR - Na Li; Yalin Huang; Xin Jin; Shuning Tan; Ruifang Wang; Zhiyu Zhang (Journal of Environmental Chemical Engineering, 2026)

Relative quantitative data of cosmetics consumption: An online survey in Guangzhou, China - Junfeng Deng; Zhen Wu; Xiaodan Lu; Xiaoyu Xian; Shixiong Zheng; Yunying Mo; Tianyang Liu; Siyu Sun; Shihan Huang; Ye Hong; Xingyu Yu; Aliya Yijiati; et al. (Regulatory Toxicology and Pharmacology, 2026)

Engineered poly (ionic liquid) hydrogel with tunable alkyl chains for multi-mode stationary phases - Shuning Li; Xiaojing Liang; Yong Guo; Shuai Wang; Licheng Wang (Analytica Chimica Acta, 2026)

Coarse Woody Debris Maintains Two Distinct and Interrelated Detrital Food Webs in Forest Ecosystems - Zhihui Wang; Yuchen Lu; Shuning Ma; Benjuan Liu; Rui Cao; Lifeng Wang; Yong Zhang; Wanqin Yang (Ecosystems, 2026)

Classification and Evaluation of a Shale Oil Reservoir in the Qingshankou Formation in the Southern Songliao Basin, NE China - Guofeng Wang; Dawei Zhang; Liang Yang; Yongqing Zhang; Junling He; Jilin Xing; Jun Jiang; Jijun Li; Shuning Zhang; Chenxu Yan; Hang You; Ketao Zheng; et al. (Journal of Earth Science, 2026)

The Effect of Mining Activities on the Hydrochemical and Isotopic Characteristic of Groundwater in the Shennan Coal Mine, Shaanxi Province, Northwest China - Ankun Luo; Shuning Dong; Hao Wang; Shouchuan Zhang; Haidong Cao; Shidong Wang; Zhongkui Ji; Xiaoyu Hu (Mine Water and the Environment, 2026)

Sequential framework integrating genetic algorithm and deep learning for multi-dimension fracture network characterization and uncertainty reduction - Zihao Wang; Zhenxue Dai; Hui Ling; Shangxian Yin; Shuning Dong; Yuzhou Xia; Hung Vo Thanh; Farzad Moeini; Mohamad Reza Soltanian; Yue Ma; Dayong Wang (Journal of Hydrology, 2026)

Microwave-triggered plasma catalysis over Cu/CuOx wires: Synergistic CO2 reduction via enhanced discharge and dynamic oxygen vacancies - Shuning Xiao; Yang Xu; Haotong Ma; Xiuwen Zhao; Hao Zheng; Shuo Wang; Zhanshuo Tao; Hexing Li (Chemical Engineering Journal, 2026)

Microwave-induced interfacial coupling boosts photocatalytic CO2-to-CO conversion over MoS2/g-C3N4 heterojunctions - Jixuan Dong; Haotong Ma; Shuo Wang; Zhanshuo Tao; Yingchun Miao; Shuning Xiao (Journal of Environmental Chemical Engineering, 2025)

Experimental investigation on the permeability evolution and mechanism of burnt rock under fluid–solid coupling conditions - Ankun Luo; Shuning Dong; Hao Wang; Xiaoming Guo; Zhongkui Ji; Tiantian Wang; Hongbo Shang; Xiaoyu Hu; Yuan Liang; Zhennan Zhu (Acta Geodaetica et Geophysica, 2025)

How does the construction industry affect economic growth and environmental quality in China? - Shenglai Zhu; Zichuan Quan; Shuning Gao; Weihao Wang; Bilal Aslam; Jikun Jiang (Clean Technologies and Environmental Policy, 2025)

Differential profiles of antibiotic resistance genes in activated sludge and biofilm in wastewater treatment plants - Haohao Sun; Weiyao Li; Shuning Zhang; Lingjue Yuan; Di Wang; Jiayue Sun; Hongyu Wang (Journal of Hazardous Materials, 2025)

Dopamine-functionalized chondroitin sulfate/gelatin-based composite hydrogels for enhancing wound healing and bone regeneration - Jian Yang; Jiale Jin; Haojie Yu; Yun Wang; Li Wang; Xiaowei Liu; Dongyu Wang; Yudi Huang; Chenguang Ouyang; Yu Wang; Yichuan Hong; Shuning Ren; et al. (Carbohydrate Polymers, 2025)

Crop rotation and organic fertilizer maintains diversity and activity of cbbL-carrying CO2-fixing bacteria in reclaimed coal mining soils - Shuning Bai; Meihua Fan; Min Wu; Xiaolong Sui; Yibo Song; Yunlong Jiang; Huisheng Meng; Yulin Liu; Xiangying Wang; Xianjun Hao; Yi Li; Jianping Hong; et al. (European Journal of Soil Biology, 2025)

Corrigendum to “Effects of carboxymethyl chitosan oligosaccharide on regulating immunologic function and inhibiting tumor growth” [Carbohydrate Polymers 250 (2020) 116994] - Zhiwen Jiang; Shuning Wang; Jun Hou; Jinhua Chi; Shuo Wang; Kai Shao; Wanshun Liu; Rongju Sun; Baoqin Han (Carbohydrate Polymers, 2025)

Insights into the synergistic mechanisms of citric acid in detoxifying cadmium in tall fescue - Jian Cui; Wenqi Ding; Shuning Li; Xuanyang Wu; Jianing Wang; Qiuyu Su; Junxiang Qi; Xiaoyang Sun; Jinmin Fu (Journal of Hazardous Materials, 2025)

A resonance energy transfer electrochemiluminescence sensor based on the synergistic effect of luminol@β-cyclodextrin and Ni-MOF@Pt NPs for the oxytetracycline detection - Li Tian; Shuning Yang; Guangping Ma; Pengfei Han; Hanyue Jiang; Wenzhuo Wang; Juan Lu (Food Chemistry, 2025)

Occurrence, ecological risk and estrogenic effect of 19 bisphenol analogues in the surface water used for drinking water in Shanghai, China - Shuning Wang; Cheng Peng; Nan Sheng; Lushi Lian; Jiayin Dai; Xiaohong Guan (Water Research, 2025)

Dual-site Langmuir-Hinshelwood mechanism in ZnCr-LDH/NH2-UIO66 heterojunction for efficient photocatalytic NO oxidation - Jing Guo; Haotong Ma; Huan Shang; Wenchao Wang; Ruiyi Yang; Shuo Wang; Yingchun Miao; David Lee Phillips; Guisheng Li; Shuning Xiao (Journal of Hazardous Materials, 2025)

Switching CO2 reduction selectivity in Cu-TiO2 catalysts: Role of Cu+ site location and oxygen vacancy concentration - Yuhan Ji; Haotong Ma; Honglei Shao; Zhanshuo Tao; Wenchao Wang; Yingchun Miao; Shuning Xiao (Environmental Research, 2025)

High-resolution DNA metabarcoding of modern surface sediments uncovers a diverse assemblage of dinoflagellate cysts in the Pacific and Arctic Oceans - Junyue Wang; Qian Liu; Shuning Huang; Kenneth Neil Mertens; Vera Pospelova; Xin Shen; Haifeng Gu (Marine Pollution Bulletin, 2025)

Enhanced low-temperature waste heat recovery in ethyl acetate / cyclohexane separation using heat integration and ORC - assisted pressure - swing distillation - Yanchao Xue; Qingrui Zhang; Shuning Jiang; Cai Wang; Qian Lin (Process Safety and Environmental Protection, 2025)

Heavy metals migration and in-situ solidification in the co-combustion of solid waste fuels: Rules and differences - Shuning Qin; Li Jia; Xiaolei Qiao; Chenxing Wang; Baihe Guo; Xinyue Chang; Peng Cheng; Yan Jin (Journal of Environmental Chemical Engineering, 2025)

Analyzing the National Park policymaking process in China from a multiple streams perspective: Domination by the political stream and policy entrepreneurs - Shuning Zhu; Weiye Wang; Jinlong Liu (Forest Policy and Economics, 2024)

Cytological and metabolomic analysis of Citrus fruit to elucidate puffing disorder - Ting Wang; Shuqi Zheng; Fuzhi Ke; Shiyi Zhang; Jinping Xiao; Xuepeng Sun; Shuning Zhang; Lanlan Zhang; Jinli Gong (Food Chemistry, 2024)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Study on regeneration mechanism of composite adsorbent by Mg-MOF-74-based modified biochar - Chenxing Wang; Li Jia; Yan Jin; Shuning Qin (Science of The Total Environment, 2024)

Uncovering the drivers of ecological footprints: A STIRPAT analysis of urbanization, economic growth, and energy sustainability in OECD countries - Zichuan Quan; Xi Xu; Jikun Jiang; Weihao Wang; Shuning Gao (Journal of Cleaner Production, 2024)

Aerobic granular sludge inoculant for enhancing high salinity wastewater treatment: Performance and value-added biopolymer recovery - Haifeng Zhang; Shuning Wang; Sudan Lin; Yuanyuan Miao; Dong-Hoon Kim; Boyan Xu; Wenfeng Du; Xueqing Shi; Shujuan Huang (Chemical Engineering Journal, 2024)

How did submarine volcanic eruptions interact with organic matter to favour hydrocarbon generation in the Bohai Bay Basin, China? - Chuanming Li; Jianhui Zeng; Shuning Liu; Yuyang Dong; Maoyun Wang (International Geology Review, 2024)

Impact of long-term mining activity on groundwater dynamics in a mining district in Xinjiang coal Mine Base, Northwest China: insight from geochemical fingerprint and machine learning - Ankun Luo; Shuning Dong; Hao Wang; Zhongkui Ji; Tiantian Wang; Xiaoyu Hu; Chenyu Wang; Shen Qu; Shouchuan Zhang (Environmental Science and Pollution Research, 2024)

Adult-type neuronal intranuclear inclusion disease with limb tremor onset: a case report - Shuning Wang; Hui Zhu; Jingyao Liu; Hongping Liu; Hongyu Gao (Acta Neurologica Belgica, 2024)

Do industrial solid waste recycling and technological innovation promote low-carbon development in China? New insights from NARDL approach - Zichuan Quan; Xi Xu; Weihao Wang; Jikun Jiang; Shuning Gao (Science of The Total Environment, 2024)

Study on the decarbonization mechanism of composite adsorbent by Mg-MOF-74-based modified biochar - Chenxing Wang; Li Jia; Shuning Qin; Ling He; Yawen Wu; Qingrui Liu; Yan Jin (Fuel, 2024)

Highly efficient removal of Aflatoxin B1 employing a flower-like covalent organic framework-based fiber membrane - Shuning Li; Kang Qin; Yixue Fu; Defu He; Dianpeng Han; Shuang Li; Yu Wang; Shuyue Ren; Yuan Peng; Zhixian Gao (Journal of Environmental Chemical Engineering, 2023)

Interference of periostin attenuates pathological changes, proinflammatory markers and renal fibrosis in diabetic kidney injury - Xiaoting Duan; Cheng Chen; Xiaoli Liu; Taoxia Wang; Shuning Feng; Jianwei Li; Guiying Li (Genes & Genomics, 2023)

Coarse woody debris and litter layer exert differential roles in nursing soil fungal communities across a subalpine forest successional series - Zhihui Wang; Fei Li; Jianfeng Hou; Xuqing Li; Rui Cao; Yurui Jiang; Yuchen Lu; Shuning Ma; Wanqin Yang (Acta Oecologica, 2023)

Impact of energy and industrial structure on environmental quality and urbanization: evidence from a panel of BRICS countries - Jikun Jiang; Shenglai Zhu; Shuning Gao; Bilal Aslam; Weihao Wang (Environmental Science and Pollution Research, 2023)

How does renewable energy, newborn birth rates, industrialization, and economic growth affect environmental quality? New evidence from 90 Belt and Road countries - Jikun Jiang; Shuning Gao; Wenyu Yuan; Weihao Wang; Bilal Aslam (Environmental Science and Pollution Research, 2023)

A bibliometric review on electric vehicle (EV) energy efficiency and emission effect research - Shengyong Yao; Zixiang Bian; Mohammad Kamrul Hasan; Ru Ding; Shuning Li; Yanfei Wang; Shulei Song (Environmental Science and Pollution Research, 2023)

Water transport in continental subduction zones: Constraints from eclogite from the Dabie orogen, east-central China - Zhi-Min Wang; Ren-Xu Chen; Yong-Fei Zheng; Shuning Li; Lin Zhu; Bing Gong; Xiang-Ping Zha; Wan-Cai Li (Journal of Asian Earth Sciences, 2023)

Phthalocyanine-mediated interfacial self-assembly of magnetic graphene nanocomposites toward low-frequency electromagnetic wave absorption - Chenchen Liu; Shuning Liu; Xiaofang Feng; Ke Zhu; Guo Lin; Zhongxiang Bai; Lingling Wang; Xiaobo Liu (Chemical Engineering Journal, 2023)

Unveiling evolution characteristics of inventive activity on climate change mitigation technologies in China - Shuning Liu; Min Wang; Qingtai Xiao (Environment, Development and Sustainability, 2022)

Application of a pump and treat system to addressing potential vapor intrusion risk in a karst terrane: design parameter optimization and performance evaluation - Shuning Dong; Hao Wang; Wanfang Zhou (Sustainable Water Resources Management, 2022)

Dynamic Characteristics of Water Inflow from a Coal Mine’s Roof Aquifer - Zhenfang Zhou; Shuning Dong; Hao Wang; Dewu Jin; Xiaodong Wang; Yang Dong; Shi Chen; Debin Li; Xingling Dong; Hongbo Shang (Mine Water and the Environment, 2022)

Directed evolution of the PobR allosteric transcription factor to generate a biosensor for 4-hydroxymandelic acid - YaoYao Liang; Juan Luo; Chenhao Yang; Shuning Guo; Bowen Zhang; Fengqianrui Chen; Kairui Su; Yulong Zhang; Yi Dong; Zhihao Wang; Hongda Fu; Guangchao Sui; et al. (World Journal of Microbiology and Biotechnology, 2022)

A quadruple recombination event discovered in hepatitis E virus - Hao Shen; Shuning Liu; Min Ding; Haixia Gu; Ming Chang; Yanshuang Li; Hua Wang; Xingwen Bai; Hongxing Shen (Archives of Virology, 2021)

The Water Resisting Properties of the Top Portion of the Ordovician Limestone Aquifer in the North China Coalfield - Hao Wang; Shuning Dong; Rui Chai; Wei Qiao; Jian Yang; Ji Liu; Linsheng Zhou; Zhenfang Zhou; Zhaoxing Liu; Hongbo Shang (Mine Water and the Environment, 2021)

Influences on the performance of cement-based grout used to reform the upper Middle Ordovician limestone in Hanxing mining area - Liu Zhaoxing; Dong Shuning; Wang Hao; Zhao Chunhu; Zhou Zhenfang (Arabian Journal of Geosciences, 2021)

Introduction to Special Issue on Mine Water Inrushes: Risk Assessment, Mitigation, and Prevention - Shuning Dong; Wanfang Zhou; Hao Wang (Mine Water and the Environment, 2021)

Discussion on Some Topical Issues of Water Prevention and Control in Coal Mines - Shuning Dong; Wenzhong Zhang; Wanfang Zhou; Rui Chai; Hao Wang; Chunhu Zhao; Xingling Dong; Qiangmin Wang (Mine Water and the Environment, 2021)

Characteristics of Water Hazards in China’s Coal Mines: A Review - Shuning Dong; Hao Wang; Xiaoming Guo; Zhenfang Zhou (Mine Water and the Environment, 2021)

Mine Water Source Discrimination Based on Hydrogeochemical Characteristics in the Northern Ordos Basin, China - Jian Yang; Shuning Dong; Hao Wang; Guoqing Li; Tiantian Wang; Qiangmin Wang (Mine Water and the Environment, 2021)

Effects of Groundwater Table Decline on Vegetation Transpiration in an Arid Mining Area: A Case Study of the Yushen Mining Area, Shaanxi Province, China - Qiangmin Wang; Shuning Dong; Hao Wang; Jian Yang; Chunhu Zhao; Xingling Dong; Tiantian Wang (Mine Water and the Environment, 2020)

Sinkholes and their impacts on karst hydrogeology in a peatland complex of Northern Ontario, Canada - Shuning Dong; Hao Wang; Wanfang Zhou (Carbonates and Evaporites, 2020)

Data Analysis and Key Parameters of Typical Water Hazard Control Engineering in Coal Mines of China - Lin Mou; Shuning Dong; Wanfang Zhou; Wei Wang; Ang Li; Zhiyuan Shi (Mine Water and the Environment, 2020)

Factors effecting the freeze thaw process in soils and reduction in damage due to frosting with reinforcement: a review - Rongfei Zhao; Shuning Zhang; Wei Gao; Jin He; Jie Wang; Dan Jin; Bo Nan (Bulletin of Engineering Geology and the Environment, 2019)

Aeromonas veronii and aerolysin are important for the pathogenesis of motile aeromonad septicemia in cyprinid fish - Chao Ran; Chubin Qin; Mingxu Xie; Jinxiong Zhang; Jie Li; Yadong Xie; Yibing Wang; Shuning Li; Lihui Liu; Xiaozhe Fu; Qiang Lin; Ningqiu Li; et al. (Environmental Microbiology, 2018)
Summary Aeromonas species are ubiquitous inhabitants of freshwater environments, and are responsible for fish motile aeromonad septicemia (MAS). A. hydrophila is implicated as the primary etiologic agent of MAS. Here, we analysed MAS epidemiological data for cyprinid fish in southern China, and found that A. veronii infections dominated. Consistent with this observation, A. veronii isolates were generally more virulent than A. hydrophila isolates when infecting germ‐free zebrafish larvae via continuous immersion challenge. Through in vivo screening of the transposon library of the A. veronii strain Hm091, aerolysin was identified as the key virulence factor. Further results indicated that A. veronii Hm091 aerolysin disrupts the intestinal barrier of zebrafish, enabling systematic invasion by not only A. veronii Hm091 in a mono‐infection, but also A. hydrophila NJ‐1 in a mixed infection. Moreover, the differences in aerolysin expression and activity were the major contributor to the observed differences between the A. veronii and A. hydrophila strains regarding invasion efficacy via intestine. Together, our results provide new insights into the aetiology and pathogenesis of Aeromonas infections, and highlight the importance of A. veronii ‐targeted treatments in future efforts against MAS.

Estrogenicity of halogenated bisphenol A: in vitro and in silico investigations - Jie Zhang; Tiezhu Li; Tuoyi Wang; Cuiping Yuan; Shuning Zhong; Tianzhu Guan; Zhuolin Li; Yongzhi Wang; Hansong Yu; Quan Luo; Yongjun Wang; Tiehua Zhang (Archives of Toxicology, 2018)

Antibiotic growth promoter olaquindox increases pathogen susceptibility in fish by inducing gut microbiota dysbiosis - Suxu He; Quanmin Wang; Shuning Li; Chao Ran; Xiaoze Guo; Zhen Zhang; Zhigang Zhou (Science China Life Sciences, 2017)